Fine particle matter disrupts the blood–testis barrier by activating TGF‐β3/p38 MAPK pathway and decreasing testosterone secretion in rat. Issue 7 (19th April 2018) - Liu, Jianhui; Ren, Lihua; Wei, Jialiu; Zhang, Jin; Zhu, Yupeng; Li, Xiangyang; Jing, Li; Duan, Junchao; Zhou, Xianqing; Sun, Zhiwei
Abstract: Fine particle matter (PM) is correlated with male reproductive dysfunction in animals and humans, but the underlying mechanisms remain unknown. To investigate the toxic mechanism of PM, 32 male Sprague‐Dawley (SD) rats were exposed to saline or PM2.5 with the doses of 1.8, 5.4, and 16.2 mg/kg.b.w. via intratracheal instillation, respectively, one time every 3 days, in total times for 30 days. Sperm concentration, hormone level, the expressions of BTB‐associated protein and the mitogen‐activated protein kinase (MAPK) pathway, tumor necrosis factor α and transforming growth factor β3 levels were detected. The results showed a decrease in sperm number, testosterone and luteinizing hormone levels and altered ultrastructure of BTB in testis of rat after exposure to PM2.5 . The protein levels of N‐Cadherin, Occludin, Claudin‐11, and Connexin‐43 were significantly decreased in the testes. TGF‐β3 content in testes showed increase, with the p‐p38/p38 MAPK ratio also increasing after PM2.5 exposure. These results demonstrate that PM2.5 restrained the expressions of BTB‐associated proteins through activating TGF‐β3/p38 MAPK pathway and decreasing testosterone secretion, and therefore lead to the damage of BTB resulting in the decrease of sperm quality, which might be the potential reasons for its negative effects on spermatogenesis and male reproduction.